Restorasi Ekosistem Berbasis Konsesi Bagi Perusahaan: Relasi Kuasa Komunitas Batin Sembilan Dengan PT Restorasi Ekosistem Indonesia - Hildayatul Rizki; Afrizal; Zainal Arifin (Yayasan Literasi Sains Indonesia, 2026)
Restoration, commonly regarded as an ecological and biodiversity conservation effort, does not always operate ideally. In practice, restoration programs often become arenas of power relations among diverse stakeholders. This study aims to examine how the Batin Sembilan Indigenous community positions itself within the power dynamics of the ecosystem restoration program in the Hutan Harapan forest in Sumatra, managed by PT Restorasi Ekosistem Indonesia (REKI). Unlike most restoration studies that emphasize ecological outcomes, this research highlights the human dimension by analyzing the interaction between local knowledge, social practices, and conservation discourses promoted by the state and corporations. Using a critical ethnographic approach and Foucauldian discourse analysis, data were collected through in-depth interviews, participatory observation, and document review. Findings reveal that power operates through legal, managerial, and epistemic mechanisms that regulate yet enable community agency. The Batin Sembilan actively negotiates their living space and identity through adaptation, resistance, and partnership strategies. The study concludes that socio-ecological restoration success requires recognizing Indigenous peoples as knowledge holders and legitimate forest managers.